The extent to which community service occupational therapists are equipped to treat patients with hand injuries and conditions - Van Stormbroek, Kirsty (Department of Health and Rehabilitation Sciences, 2015)
South Africa is one of the most violent nations in the world and has an extremely high incidence of road accidents and work place injuries. The precise effect of this on upper limb injury statistics is not known as the incidence and prevalence of these conditions has yet to be determined. Hand injuries are, however, common worldwide and, in South Africa, may be complex in nature. This places a demand on occupational therapy services to provide comprehensive upper limb rehabilitation, a responsibility that inevitably falls on novice occupational therapists at some point. Occupational therapists in South Africa are required to complete a year of compulsory Community Service after graduating before they are permitted to practice independently. These placements are often in rural, under-resourced areas and graduates are faced with multiple new roles while negotiating the transition into practice. No published research to date has described the general experience of Community Service occupational therapists in South Africa or the extent to which these therapists are equipped to treat patients with upper limb injuries and conditions. The study sought to determine the extent to which Community Service occupational therapists are equipped to treat patients with upper limb injuries and conditions.